Arcetri, 1934: A new road for the Sciences - Mazzoni, Massimo (Il Colle di Galileo, 2021)
The current access road to the Arcetri hill, an area that has been dedicated to scientific research since the late 19th century, was given its final shape during work performed in 1933-34. The project was carried out above all thanks to the involvement of the Director of the Optics Institute, the physicist Vasco Ronchi. The work took place following a long bureaucratic struggle with the Intendenza di Finanza, the agency in charge of state property, and with the Faculty of Sciences, although the project had the support of the Chancellor De Vecchi. On the strength of documents from the Historical Archive of the University of Florence, we are able to reconstruct the stages of the operation.